2023
DOI: 10.3390/ijms24065880
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA CircCDKN2B−AS_006 Promotes the Tumor-like Growth and Metastasis of Rheumatoid Arthritis Synovial Fibroblasts by Targeting the miR−1258/RUNX1 Axis

Abstract: Rheumatoid arthritis (RA) is an autoimmune polyarthritis in which synovial fibroblasts (SFs) play a major role in cartilage and bone destruction through tumor−like proliferation, migration, and invasion. Circular RNAs (circRNAs) have emerged as vital regulators for tumor progression. However, the regulatory role, clinical significance, and underlying mechanisms of circRNAs in RASF tumor−like growth and metastasis remain largely unknown. Differentially expressed circRNAs in synovium samples from patients with R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…There are consistent data indicating that the conjuncture of genetic predisposal, environmental insults, and hormonal disequilibrium may lead to the activation of the resting epithelium, the upregulation of toll-like receptors (TLRs) such as TLR-2, 3, 4, 7, 8, and 9 [182][183][184][185], leading to the release of alarmins and pro-inflammatory cytokines such as interferon (IFN), TNF-α, IL-6 and IL-17 further promoting downstream autoimmune inflammation [184,186], ultimately resulting in the atrophy and fibrosis of the salivary glands (SG) (Figure 4) [187,188]. Over the past 15 years, several lines of evidence seem to indicate that RA-FLSs may, at least in part, undergo EMT-like process (Table 1) [31,170,171]. This conclusion was indeed supported by immunohistological analysis of both healthy and RA synovium that showed the presence of α-SMA, a myofibroblast marker responsible for collagen accumulation in fibrosis exclusively in the synovial lining layer of RA patients [31,171,172].…”
Section: Sjögren's Syndromementioning
confidence: 99%
See 4 more Smart Citations
“…There are consistent data indicating that the conjuncture of genetic predisposal, environmental insults, and hormonal disequilibrium may lead to the activation of the resting epithelium, the upregulation of toll-like receptors (TLRs) such as TLR-2, 3, 4, 7, 8, and 9 [182][183][184][185], leading to the release of alarmins and pro-inflammatory cytokines such as interferon (IFN), TNF-α, IL-6 and IL-17 further promoting downstream autoimmune inflammation [184,186], ultimately resulting in the atrophy and fibrosis of the salivary glands (SG) (Figure 4) [187,188]. Over the past 15 years, several lines of evidence seem to indicate that RA-FLSs may, at least in part, undergo EMT-like process (Table 1) [31,170,171]. This conclusion was indeed supported by immunohistological analysis of both healthy and RA synovium that showed the presence of α-SMA, a myofibroblast marker responsible for collagen accumulation in fibrosis exclusively in the synovial lining layer of RA patients [31,171,172].…”
Section: Sjögren's Syndromementioning
confidence: 99%
“…A pre-clinical study on CIA rats confirmed the role of circCDKN2B−AS_006 in the proliferative and invasive phenotype of RA-FLSs, whereas its knockdown alleviated the severity of arthritis. Mechanistic analysis concluded that circCDKN2B−AS_006 promoted EMT-like processes in RA-FLSs by inducing the expression of runt-related transcription factor 1 (Runx1), ultimately activating the Wnt/β−catenin signaling pathway (Table 1) [170]. sion of runt-related transcription factor 1 (Runx1), ultimately activating the Wnt/β−catenin signaling pathway (Table 1) [170].…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
See 3 more Smart Citations